Enhancing Problem Solving Skills in Operational Research: the Well-Structured Problem Case Study. - Cheng, Sheila; Siow, Heng Loke (2014)
The rapid development of the technology has continually increased the complexity of problems as the industries and society progress. Moreover, many studies have indicated that Malaysian graduates do not possess the required problem solving skills to meet these industrial and societal demands. In fact, the crux of Operations Research (OR) is to help people to make better and informed decision by providing a quantitative basis for decision. Furthermore, one of the significant OR characteristics is generally applied to problems, specific and localized in nature.Henceforth, the problem solving skills of Malaysian graduates could be enhanced if they learn how to solve OR problems effectively in their formal education. This paper explores the cognitive processes adopted by 42 Malaysian business degree undergraduates (BDU) in solving a well-structured (WS) OR problem. In-depth observations and interviews were conducted. The problem solving sessions using the ‘think aloud’ approach were audio- and video-recorded. The cognitive processes of the problem solvers were determined from their behavior and performance exhibited while they were delineating the concepts, proposition and strategies in their solution paths. The similarities and differences of solution paths adopted by the successful and unsuccessful problem solvers were also discussed. The findings from this study reveal that non-linear cognitive processes were adopted by the majority of the solvers. Successful solvers could recall, retrieve and relate the relevant concepts to the problem, while unsuccessful solvers were unable to comprehend the problem although they indicated that they had learnt the relevant concepts and knowledge. It is envisaged that due to the lack of acceptance in the past, these OR research findings could enlighten the academic community of the importance of equipping problem solving skills among Malaysian BDU students.